2022
DOI: 10.3390/en15030862
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Recent Advances of Additive-Improved Mg(BH4)2 for Solid-State Hydrogen Storage Material

Abstract: Recently, hydrogen (H2) has emerged as a superior energy carrier that has the potential to replace fossil fuel. However, storing H2 under safe and operable conditions is still a challenging process due to the current commercial method, i.e., H2 storage in a pressurised and liquified state, which requires extremely high pressure and extremely low temperature. To solve this problem, research on solid-state H2 storage materials is being actively conducted. Among the solid-state H2 storage materials, borohydride i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…The most detailed study on this issue was published by Yartys and co-workers who applied in situ X-ray diffraction to reveal the phase evolution of different Mg-based systems during hydrogentation-dehydrogation; however, no data are available on the crystallite size during isothermal absorption [75,76]. For more complex systems, such as Mg-TM [77] or complex hydrides [78], hydrogen uptake is usually a multi-step process; therefore, fitting the absorption curve by a single function is not possible.…”
Section: Resultsmentioning
confidence: 99%
“…The most detailed study on this issue was published by Yartys and co-workers who applied in situ X-ray diffraction to reveal the phase evolution of different Mg-based systems during hydrogentation-dehydrogation; however, no data are available on the crystallite size during isothermal absorption [75,76]. For more complex systems, such as Mg-TM [77] or complex hydrides [78], hydrogen uptake is usually a multi-step process; therefore, fitting the absorption curve by a single function is not possible.…”
Section: Resultsmentioning
confidence: 99%
“…In order to foresee any use in automotive hydrogen storage systems, it would be optimal to allow H desorption from the materials using only residual heat from a fuel cell; some modeling proposed a dehydrogenation enthalpy of 27 kJ molH 2 –1 as an optimal value for this application . To achieve reversible operations at more practical conditions with complex metal hydrides, catalysts and additives are normally used. Two other strategies more recently explored to achieve realistic operation conditions are the destabilization of the lightweight complex hydrides using a second hydride (the so-called reactive hydride composites , ) and the nanoconfinement of the hydride to modify the kinetics and/or thermodynamics . It is also worth remarking here that several metal hydride materials involve safety risks (burning when exposed to air/water, toxicity, skin burns, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic barriers of complex hydrides can be significantly reduced using various types of catalysts, and there have been several reviews describing the kinetic modification of complex hydrides by adding catalysts to NaAlH 4 , , LiAlH 4 , LiBH 4 , and Mg­(BH 4 ) 2 . In particular, the kinetics of NaAlH 4 has been extensively studied since it allows pure H 2 release and exhibits a good cyclability upon a proper modification, and numerous works demonstrated that the dehydrogenation kinetic barrier of NaAlH 4 can be reduced by employing catalyst doping or nanoconfinement.…”
Section: Fundamentals Of Thermodynamic and Kinetic Barriers For Hydro...mentioning
confidence: 99%